STABILIZATION OF FRESH BUFFALO MILK BY ACTIVATING LACTOPEROXIDASE SYSTEM - Kakar; M. U. H.; M. A. Kakar; M. N. Shahwani; N. Ahmed; M. A. Arain; M. Khaskhaili (Journal of Animal and Plant Sciences, 2013)
The aim of this study was preservation of buffalo raw milk by the activation of their natural lactoperoxidase system to extend shelf life at different temperatures. Milk samples treated with equal concentration of sodium thiocyanate ions and hydrogen peroxide i.e. 10, 20 and 30 ppm and stored at 35, 40 and 45 0C. A total of 30 fresh raw milk samples frombuffalo were used for the present study. For each treatment group, 10 raw milk samples at different temperatures were used for acidity, pH, clot on boiling test (COB), alcohol test, methylene blue reduction and thiocyanate values. Each test was performed from 0 to 9 hours with an interval of three hours except thiocyanate values, which was recorded initially and at curdling. Acidity percentage was analyzed at 350C for 0 h, 3 h, 6 h and 9 h. At 6 h and 9 h; all the combinations were significantly (P<0.01) different, except 0 ppm versus 10 ppm at 9 h. At 400C for 0 h, 3 h, 6 h and 9 h. All the combinations were significantly different at 0 h and 3 h except 20 ppm versus 30 ppm. The remaining combinations were significantly (P<0.01) different pH were significantly (P<0.05) different at 0 h between 0 ppm versus 30 ppm, 10 ppmversus 20 ppm; at 3 h, 20 ppm versus 30 ppm; at 6 h and 9 h all the combinations. The remaining combinations were highly significant (P<0.01) from each other. Thiocyanate at 350C, 400C and 450C there was significant difference (P<0.01, P<0.001) at all the stages except at 10 ppm and 30 ppm at 350C. Clot on boiling test at 350C and 400C, 10 ppmand 30 ppm at 3 h, and 20 ppm COB started positive at 4 h. Alcohol test of the samples were positive for control and 10 ppm at 6 h and for 20 ppm at 7 h respectively. At 400C, for 10 ppm, 20 ppm and control the positive reaction started at 3 h. At 450C, the reaction was positive at 1 h for control, at 3 h for 10 ppm and at 6 h for 20 ppm and at 8 h for 30 ppm. Methylene blue reduction test of the control samples were positive at 3 h. At 350C, for 10 ppm, 20 ppm and 30 ppmpositive reaction started at 5 h, 7 h and 7 h respectively. At 400C, for 10 ppm, 20 ppm and 30 ppm positive reaction started at 1 h, 2 h and 2 h respectively. And at 450C, for 10 ppm, 20 ppm and 30 ppm positive reaction started at 2 h, 5 h and 6 h respectively. Milk samples stabilized with 30 ppm were acceptable up to nine hours as compared to control which curdled within seven hours post milking. In Pakistan preservation of buffalo raw milk can be carried out by its lactoperoxidase enzyme system, which helps in collection of milk of high quality from widely scattered remote areas. The study suggests that in stabilized samples, the changes in pH were slight up to 9 hours post-preservation, which might be due to the optimum activation of LP system. Milk samples stabilized with 30 ppm were acceptable up to nine hours as compared to control which curdled within seven hours post milking.
Keywords: Milk; buffalo; dairy production; lactoperoxidase system; preservation